Laser annealing of semiconductor materials for future electron device application - Ong, Chio Yin. (2011)
Laser annealing (LA) is an emerging technique that has the potential to be incorporated into the device fabrication process in the near future. The unique characteristics of LA that are not found in the conventional thermal annealing methods have gained substantial attraction for applications to the emerging device fabrication. One of the key features of LA is that it provides ultra-fast and very high temperature annealing on localized surface region with minimum affects on the substrate. This feature is important for nanoscale device fabrication as it increases the process window and reduces the thermal budget of the related process. In addition, spatial control can be achieved by adjusting the beam size, which enables the realization of localized heating and melting. In this work, we have explored the application of LA to the semiconductor field for the future technologies. The formation of alloy from group IV semiconductors as well as group III-V semiconductors by LA was investigated. In addition, dopant activation by LA in III-V semiconductors as well as in group IV alloy semiconductors was studied.